Agro-Logistics in Central America : A Supply Chain Approach - World Bank (Washington, DC, 2017)
This chapter uses supply chain analysis (SCA) to identify transport and logistics bottlenecks that add costs, times and uncertainty to the exportation of perishable agricultural products from Central America. Macro-level analyses of logistics performance, including the logistics performance index, Doing Business Reports and Enterprise Surveys of the World Bank, as well as the Global Competitiveness Index of the Global Economic Forum, often leave policy-makers unclear on exactly what poor performance means for exporters and producers in Central America. How does poor road quality eat away at the profit margins of my country's producers? Extensive procedures add time to export processes, but how much time? How and to what extend does this additional time hurt the competitiveness of key industries? How does this effect vary by product type? By tracking the movement of seven carefully selected exports, these supply chains complement macro-level analyses by answering these questions for some of the region's key agricultural exports. A range of unique characteristics makes the success of perishable exports exceedingly dependent on the efficiency of the related logistics systems and the ability to connect effectively and reliably to global supply chains. Remote production zones add cost, time and variability to transport from the farm gate to the distribution, collection or processing center. Increasingly complicated international sanitary and phytosanitary standards (SPS) add institutional and procedural complexity to the supply chain. Above all, the time sensitivity of most perishable products increases the value of time and makes cold chain infrastructure and the availability of refrigerated containers essential for successful exportation.